2012
DOI: 10.4012/dmj.2010-091
|View full text |Cite
|
Sign up to set email alerts
|

Surface textures of composite resins after combined wear test simulating both occlusal wear and brushing wear

Abstract: The purpose of this study was to investigate the relation between the texture of worn surfaces of composite resins and the maximum wear depth. Three types of composite resins were investigated: a hybrid composite resin consisting of irregular-shaped inorganic filler particles (APX); a composite resin which contained small, irregular-shaped, inorganic filler particles and large organic composite filler particles (SRE); and another which contained spherical inorganic filler particles and large organic composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The surfaces of carefully polished dental restorations can be compromised by subsequent home care, including toothbrushing. Most studies of the effects of toothbrushing and polishing on dental restorations concluded that restoration surfaces are smoother before polishing or toothbrushing and tend to increase in roughness afterward (10,15,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The surfaces of carefully polished dental restorations can be compromised by subsequent home care, including toothbrushing. Most studies of the effects of toothbrushing and polishing on dental restorations concluded that restoration surfaces are smoother before polishing or toothbrushing and tend to increase in roughness afterward (10,15,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of a low surface roughness is an important factor related to surface gloss retention when composites are submitted to toothbrushing (O'Neill et al, ; Shimokawa et al, ). Therefore, surface roughness can influence staining, discoloration, and overall esthetics (Furuse, Gordon, Rodrigues, Silikas, & Watts, ), as well as biofilm accumulation (Cazzaniga, Ottobelli, Ionescu, Garcia‐Godoy, & Brambilla, ; Sturz, Faber, Scheer, Rothamel, & Neugebauer, ), and surface wear (Kakuta, Wonglamsam, Goto, & Ogura, ) of composite fillings.…”
Section: Introductionmentioning
confidence: 99%
“…5, the amount of large fillers containing MLV seems to be more than other materials, and cracks were observed around fillers after 40,000 cycles. These protruded large fillers might have experienced greater friction with medium or the stylus tip during each wear testing, which led to accelerative wear, as shown in previous studies 6,12,16,17,19,20) . Although the two-body wear test in the current study was carried out without medium, the exfoliated fillers may have acted as an abrasive medium.…”
Section: Discussionmentioning
confidence: 89%